1994
DOI: 10.1037/h0080321
|View full text |Cite
|
Sign up to set email alerts
|

The effects of direct involvement in goal setting on rehabilitation outcome for persons with traumatic brain injuries.

Abstract: Sixteen adults with traumatic brain injuries participated in an eight-week goal setting training program designed to assess the effects of direct involvement in goal-setting on treatment outcome. Participants were randomly assigned to either a condition designed to facilitate high involvement (HI) in goal setting or to a low involvement (LI) condition. From pretesting to posttesting, both HI and LI participants significantly improved in attaining their goals. However, at the two-month follow-up, HI participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(22 citation statements)
references
References 19 publications
4
18
0
Order By: Relevance
“…Moreover, reductions may be related to the use of data based feedback, as opposed to verbal feedback based on staff perceptions of behaviour patterns. If data based feedback was significant for obtaining the present results, it would support the position of Webb and Glueckauf [17], that systematically recording daily progress on specific goals, as opposed to verbal reporting, may contribute to successful outcomes. Lastly, questions remain regarding whether it is necessary that feedback be provided by a psychologist experienced with brain injury and patient education/counselling or could other professionals or paraprofessionals present feedback equally well.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Moreover, reductions may be related to the use of data based feedback, as opposed to verbal feedback based on staff perceptions of behaviour patterns. If data based feedback was significant for obtaining the present results, it would support the position of Webb and Glueckauf [17], that systematically recording daily progress on specific goals, as opposed to verbal reporting, may contribute to successful outcomes. Lastly, questions remain regarding whether it is necessary that feedback be provided by a psychologist experienced with brain injury and patient education/counselling or could other professionals or paraprofessionals present feedback equally well.…”
Section: Discussionsupporting
confidence: 60%
“…The findings of the investigation parallel the results of other investigations' use of systematic feedback in neurorehabilitation. For exam ple, Webb and Glueckauf [17] found that involving persons with traumatic brain injuries in treatment goal setting and using progress data led to higher ratings of goal attainment. Such effects parallel the general improvements observed in health related behaviour with self-monitoring techniques (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the process of goal negotiation and scaling, using GAS, acts as an intervention on its own. Another study compared a group of people with TBI who undertook a programme of high involvement in goal planning and weekly monitoring of progress and self-rating of GAS goals, with a group with low involvement in goal planning [42]. This study found that the high involvement group maintained gains on the GAS at 2 months follow-up, whereas the low involvement group regressed to pre-testing levels, suggesting the high involvement group continued to self monitor their own goal performance after the intervention ceased.…”
Section: Discussionmentioning
confidence: 99%
“…The RCTs using metacognitive strategy instruction have similar components and comprise goal-management training (GMT), 55,56 goal-setting, 57 time-pressure management, 58 meta-componential approach, 48 multifaceted strategy training, 49 and training in problem orientation and problem solving. Most of the interventions incorporate metacognitive strategy instruction/training and contain multiple components (eg, goal identification, direct feedback, strategy use), an exception being the randomized crossover design by Wilson et al 54 using an external aid (paging system) for people with impairments in planning and memory functions.…”
Section: Recommendationsmentioning
confidence: 99%